2018
DOI: 10.1002/brb3.951
|View full text |Cite
|
Sign up to set email alerts
|

Sodium valproate compared to phenytoin in treatment of status epilepticus

Abstract: BackgroundStatus epilepticus (SE) is a neurological emergency which can be life‐threatening. Several medical regimens are used in order to control it. In this study, we intended to evaluate the clinical efficacy and tolerability of sodium valproate and intravenous phenytoin (IV PHT) in the control of SE.MethodsOne hundred and ten consecutive patients suffering from benzodiazepine refractory SE who were referred to the emergency ward from March 2014 to March 2015 were randomly divided into two groups. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…In a class III study of 110 adults with established SE, control was 78% for VPA 30 mg/kg versus 71% for PHT 20 mg/kg ( P = NS). 163 Mundlamuri et al reported a class III study of 150 adults with established CSE, 29% of whom progressed to RSE. 10 After first receiving 4 to 6 mg of LZP, patients were randomized 1:1:1 to receive a loading dose of LEV 25 mg/kg, PHT 20 mg/kg, or VPA 30 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…In a class III study of 110 adults with established SE, control was 78% for VPA 30 mg/kg versus 71% for PHT 20 mg/kg ( P = NS). 163 Mundlamuri et al reported a class III study of 150 adults with established CSE, 29% of whom progressed to RSE. 10 After first receiving 4 to 6 mg of LZP, patients were randomized 1:1:1 to receive a loading dose of LEV 25 mg/kg, PHT 20 mg/kg, or VPA 30 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 659 records was identified by database and trial registers searching (303 MEDLINE, 285 CENTRAL, 21 Opengrey.eu, and 50 ClinicalTrials.gov). After excluding duplicates and reading title and abstracts, 6 RCTs were initially included [13][14][15][16][17][18]. One study comparing VPA with PHT [13] was eventually excluded, as it provided data on SE control within 7 days of administration and this time cut-off was considered to be too long to be clinically meaningful.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled RR for the cessation of seizures (10 RCTs, n = 1,012) ( 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ) was statistically significant (RR 0.89; 95% CI, 0.82–0.97) (Fig. 3A ), showing the superior effect of other medications compared to PHT.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 1,103 studies from the electronic databases, and 1,090 studies were excluded because they were not RCTs. Finally, the full texts of 13 studies were reviewed, and 10 studies 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 were included in the final analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation